PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN - Lestari, Keukeu Firda; Tanuatmodjo, Heraeni; Mayasari, Mayasari (Business Education Program of Universitas Pendidikan Indonesia, 2016)
The problem of this research was about decrease in dividend policy BUSN Devisa listed on the Indonesia Stock Exchange which is measured by Dividend Payout Ratio (DPR) over the last two years. These factors affecting the dividend policy were liquidity which is measured by Loan to Deposit Ratio (LDR) and profitability which is measured by Return On Equity (ROE). The purposes of this study were describing the liquidity, profitability, dividend policy, the effect liquidity on dividend policy, the effect profitability on dividend policy, and the effect of liquidity and profitability on dividend policy. This research utilised descriptive and verificative, the technique which is used was multiple correlation, and hypothesis testing used t Test (partial significance test) and F Test (simultaneous significance test). The data is gained from secondary data which is from the annual report and summary of performance BUSN Devisa from 2010-2014. The population of this study was 25 BUSN Devisa listed on the Indonesia Stock Exchange with 4 samples through purposive sampling technique. The result of hypothesis testing in partial showed that liquidity and profitability effected the dividend policy significantly. The result of hypothesis testing showed that the liquidity and profitability effected on dividend policy significant simultaneously.Keywords: Liquidity, Profitability, Dividend Policy